Cultivation of Sudan grass in different ways of economic use of West Kazakhstan - Nasiyev, B. N.; Yancheva, H. G.; Zhanatalapov, BN. Zh. (News of the National Academy of Sciences of the Republic of Kazakhstan /series of agrarian sciences-2019, 2019)
The aim of the research is to study the technology of cultivation of Sudan grass to provide livestock production with full feed. As a result of the conducted researches, data on efficiency and fodder value of Sudan grass in the conditions of West Kazakhstan region at cultivation for green forage, hay and haylage were obtained by means of selection of optimum term of harvesting. Целью исследований является изучение технологии возделывания суданской травы для обеспечения животноводства полноценными кормами. В результате проведенных исследований получены данные по продуктивности и кормовой ценности суданской травы в условиях Западно-Казахстанской области при возделывании на зеленый корм, на сено, на сенаж посредством подбора оптимального срока уборки.
Keywords: rk; feed production; отечественное издание; научный журнал; периодическое издание; журнал коксон; sudan grass; harvesting time; green feed; hay; haylage; yield; feed value; кормопроизводство; суданская трава; срок уборки; зеленый корм; сено; сенаж; урожайность; кормовая ценность